IMPLEMENTASI RFID DI LINGKUP KEBENCANAAN DALAM MENGURANGI WAKTU TUNGGU PEMBAGIAN BANTUAN - Banu Santoso; Windyarto Aziz Assidiqie; Marti Widya Sari (JITEK (Jurnal Ilmiah Teknosains), 2022)
Data collection system Distribution of disaster relief aid in evacuation centers which is still carried out conventionally where data collection on the identity of disaster victims will be recorded on a sheet of paper during the entry process at the refugee barracks, resulting in long queues and making it less conducive when distributing aid, it is necessary to design a system data collection service distribution of assistance to record the identity of disaster victims by using Radio Frequency Identification (RFID) in the form of a bracelet, by applying single-phase and multi-channel single-phase queuing models and using the prototyping method. The purpose of this research is to reduce the waiting time for the distribution of aid, so that there is no queue buildup. a data collection system with a conventional single-channel single-phase model should take 16 seconds, while a data collection system for distribution of assistance integrated with RFID takes only 2 seconds, while a data collection system for distribution of assistance with a conventional multi-channel single-phase model takes 22 seconds and which uses RFID takes 2 seconds. The trial results show that the distribution of assistance is faster when using a single-phase multi-channel queuing model.